2017
DOI: 10.11144/javeriana.sc22-2.eazp
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and zooplankton parameter changes during the drying of a saline shallow temporary lake in central Argentina

Abstract: Central Argentina has numerous saline lakes sustained by groundwater sources and rainfall. These lakes are temporary and experience significant changes in water level and salinity, depending on wet and dry climate cycles. This study aims to investigate the scarcely known dynamics of environmental and zooplankton parameters during the drying phase of one of these lakes. Monthly samples were taken from December 2 012 to July 2 013 in the Ojo de Agua Uriburu lake, previous to its drying. At the beginning of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies have reported the sensitivity responses of zooplanktonic assemblages to environmental changes (Branco et al, 2007;Hébert et al, 2017;Vignatti et al, 2017;Oh et al, 2017). Considering the attributes of ecologically relevant species, functional diversity is a good predictor of processes and ecosystem functioning (Tilman et al, 1997;Barnett et al, 2007;Hébert et al, 2017), since this measure considers the attributes of a species and the impact thereof on the local ecosystem (Hébert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the sensitivity responses of zooplanktonic assemblages to environmental changes (Branco et al, 2007;Hébert et al, 2017;Vignatti et al, 2017;Oh et al, 2017). Considering the attributes of ecologically relevant species, functional diversity is a good predictor of processes and ecosystem functioning (Tilman et al, 1997;Barnett et al, 2007;Hébert et al, 2017), since this measure considers the attributes of a species and the impact thereof on the local ecosystem (Hébert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their phytoplankton communities are generally dominated by cyanobacteria which generally bloom during the warm season (Quirós et al 2002, Izaguirre et al 2015) as a result of water level fluctuations and eutrophication, or early spring depending on zooplankton grazing and light limitation (Torremorell et al 2007). The western part of this region is located below the 700 mm/year isohyet (Diovisalvi et al 2015) with mainly temporary, shallow, and saline lakes (Vignatti et al 2017), with water level fluctuations depending on precipitation cycles (Viglizzo 2011). Some of these lakes had uncommon fall/winter chlorophyll peaks but no affecting factors were associated to them (Echaniz et al 2013, Echaniz et al 2016.…”
Section: Introductionmentioning
confidence: 99%